Pollutants Generated by the Combustion of Solid Biomass Fuels - Jones, Jenny M.; Lea-Langton, Amanda R.; Ma, Lin; Pourkashanian, Mohamed; Williams, Alan (SpringerBriefs in Applied Sciences and Technology, 2014)
XVI, 109 p. 38 illus.